"Teacher's Skills in Teaching and Educating Elementary School Students with Disabilities" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the opinions of our country and foreign scientists are mentioned regarding the improvement of the teacher's skills in providing education and training to the primary school students with limited opportunities.